A study on kitchen spatial layout of food truck in Klang Valley - Nuur Hafizah Ramdan (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2020)
Food and Beverages (F&B) industries are now turning into mobile vendor, including food truck as new and promising business proposition. The strategy of setting up easy and fast food to serve from vehicles is known as food truck. However, despite the fact that food truck is adopting compact kitchen from restaurant to mobile kitchen, the food preparation in a compact space shows different concern which on space utilization and safety. This research aim to study the spatial element in the food truck kitchen's spatial focusing on Klang Valley area and to propose the design recommendation for food truck kitchen.Therefore, the objectives of this research are 1) to investigate the spatial elements in the food truck kitchen in selected area in Klang Valley 2) to propose a design recommendation for food truck kitchen. 2 phases of survey were done which are pilot survey (survey A) and main survey (survey B). 32 food trucks samples were selected based on popularity in the search engine by using term of “food truck”. Data collection has been analyzed on the types of food trucks by line up analysis to categorize the type of menu served and location. The number of movements during food preparation were analyzed as well to obtain the work triangle ratio. Therefore ,8 elements have been identified as the factors that influenced the food truck kitchen layout design which are; menu on the truck ; equipment used ; food preparing behavior ; type of kitchen; work triangle; number of worker, air ventilation and type of cabinet. The result revealed that there are 3 types of menu which are fusion cuisine western cuisine and beverages. The western fusion showed the highest number of movement during food preparation. The more numbers of preparation movements shows that the preparation of the meal was more complicated. This study also found that there are food truck workspace with work triangle and without work triangle. The wider work triangle in the kitchen will give a better workspace for food preparation. Most of the food trucks samples have ideal work triangle. However, many food truck samples still having discomfort working space such as collision. Thus, this study proposed a design recommendation for food truck kitchen spatial that consist of 8 elements which are , 1) to categorized the menu, 2) to list the compulsory equipment needed for food truck kitchen, 3) to determine what is meal preparing zoning in the kitchen 4) determine the type of kitchen ( there are 4 types), 5) installing mounted cabinet 6) create bigger and even work triangle based on meals preparation behavior 7) to have only 2 maximum workers at 1 shift, and 8) to install exhaust fan especially on fusion and western cuisine food truck. The research on design recommendations for the food truck kitchen spatial is hope to be considered by food truck vendors, the agencies and government to use this as a basic guideline and hopefully all activities in the food truck kitchen can be done smoothly in a safe and healthy work environment.